2019
DOI: 10.3168/jds.2018-15367
|View full text |Cite
|
Sign up to set email alerts
|

Symposium review: Re-evaluation of National Research Council energy estimates in calf starters

Abstract: Provision of nutrients in appropriate amounts to meet nutrient requirements for growth, production, and reproduction is the basis for modern animal nutrition. Ration formulation systems predict nutrient requirements based on numerous inputs and then predict nutrient supply based on predicted intake and nutrient content of feeds. Energy systems are used to predict energy supply based on gross caloric content of feeds followed by adjustments for digestion and metabolism of ingested energy. Many models of energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
3
5
0
Order By: Relevance
“…Thus, different EO can exert different effects on nutrient digestibility. These digestibility coefficients are within the ranges and similar to those recently published by Quigley (2019).…”
Section: Nutrient Digestibilitysupporting
confidence: 90%
“…Thus, different EO can exert different effects on nutrient digestibility. These digestibility coefficients are within the ranges and similar to those recently published by Quigley (2019).…”
Section: Nutrient Digestibilitysupporting
confidence: 90%
“…Previous studies have suggested that a comparatively low number of amino acids and peptides may be absorbed and metabolized by the rumen tissue ( 88 ). However, the development of the rumen epithelium requires increased cell and protein turnover ( 25 , 89 ). In the present study, many upregulated DEGs in the ES + EW group were annotated in pathways related to amino acid metabolism, including biosynthesis of amino acids, cysteine and methionine metabolism, arginine and proline metabolism, valine, leucine, and isoleucine degradation; glycine, serine, and threonine metabolism; and lysine degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing forage in rations reduced total DFI, as indicated by the negative coefficient for PctForage in both nonlinear and linear models. Reduced DFI with increasing forage in the diet has been reported (Hill et al, 2008;2010b, 2019, although others reported increasing DFI with forage in the diet (Coverdale et al, 2004;Khan et al, 2011b). Measurement of long forage intake is often difficult and may increase error associated with DFI measurements.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the 2001 Dairy NRC model assumes that DFI is the amount of feed required to provide ME to achieve a target rate of ADG (NRC, 2001). Because it has been shown recently that the ME in CS is not a fixed value (Quigley, 2019;Quigley et al, 2019a,b), prediction of the contribution of ME from dry feed may be difficult, thereby confounding prediction of DFI.…”
Section: Introductionmentioning
confidence: 99%